2019
DOI: 10.1038/s41467-019-12774-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding while chaperone bound is dependent on weak interactions

Abstract: It is generally assumed that protein clients fold following their release from chaperones instead of folding while remaining chaperone-bound, in part because binding is assumed to constrain the mobility of bound clients. Previously, we made the surprising observation that the ATP-independent chaperone Spy allows its client protein Im7 to fold into the native state while continuously bound to the chaperone. Spy apparently permits sufficient client mobility to allow folding to occur while chaperone bound. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 54 publications
3
43
0
2
Order By: Relevance
“…In this mechanism, substrate release is not a prerequisite for substrate folding. We have found that the folding-while-bound mechanism is dependent on relatively weak chaperone–substrate interactions 9 . Variants of Spy that bind SH3 with stronger affinity than does wild-type (WT) Spy significantly slow the folding of bound substrate 9 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this mechanism, substrate release is not a prerequisite for substrate folding. We have found that the folding-while-bound mechanism is dependent on relatively weak chaperone–substrate interactions 9 . Variants of Spy that bind SH3 with stronger affinity than does wild-type (WT) Spy significantly slow the folding of bound substrate 9 .…”
Section: Introductionmentioning
confidence: 92%
“…We have found that the folding-while-bound mechanism is dependent on relatively weak chaperone–substrate interactions 9 . Variants of Spy that bind SH3 with stronger affinity than does wild-type (WT) Spy significantly slow the folding of bound substrate 9 . The substrates of Spy tested so far have been small, topologically simple, all β-sheet or all α-helical model proteins.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…En la región cóncava es donde interaccionan las proteínas sustrato. Esta región tiene cuatro zonas hidrofóbicas rodeadas de aminoácidos hidrofílicos con carga positiva, pertenecientes a la región N-terminal flexible y al asa que conecta H1 con H2 (Koldewey et al, 2017;Kwon et al, 2010;Wu, Stull, Lee & Bardwell, 2019)…”
Section: Spyunclassified
“…La proteína Spy ha sido muy estudiada y sirve como modelo de la interacción chaperona/proteína sustrato. Esto se debe al tamaño pequeño de Spy y a que se han identificado algunos de sus sustratos específicos, como la proteína Im7 (Wu et al, 2019). El mecanismo por el que Spy favorece el plegamiento de otras proteínas se debe a que la proteína sustrato se une a la chaperona a partir de interacciones electrostáticas transitorias de largo alcance.…”
Section: Spyunclassified